Description of the Psychological Adaptation Response of HIV/AIDS Sufferers in Accepting HIV/AIDS in the Spirit of the Pelangi Community of Nganjuk Regency - Erni Tri Indarti; Puji Astutik; Galih Caesar Rini (Journal for Research in Public Health, 2025)
HIV/AIDS sufferers experience changes in psychological responses including sadness, loss of hope, helplessness, loss of self-esteem and social identity, which gives rise to feelings of worthlessness. The psychological adaptive response is self-acceptance when experiencing an illness, which will generate various feelings and reactions. The aim of the research was to determine the Psychological Adaptation Response of HIV/AIDS Sufferers in Accepting HIV/AIDS in the Spirit Pelangi Community, Nganjuk Regency. This research uses Descriptive research design, the research was carried out from 10th to 17th January 2024 in the Spirit Pelangi Community, Nganjuk Regency. The population is 48 HIV/AIDS sufferers who have just been detected in the Spirit Pelangi Community, Nganjuk Regency. The sample was 39 respondents, with purposive sampling technique. The variable used is the Psychological Adaptation Response of HIV/AIDS Sufferers in Accepting HIV/AIDS. Data collection techniques using questionnaires. The results of the research showed that of the 39 respondents, the majority, namely 23 respondents (58.97%) experienced a maladaptive psychological adaptation response, and almost half, namely 16 respondents (41.03%) experienced an adaptive psychological adaptation response. Based on research, most respondents experienced maladaptive psychological adaptation responses. Factors that influence the psychological adaptation response are gender, age, education level, social problems, and family support. Some of these factors are that family support has a very important role for HIV/AIDS sufferers because good family support will increase self-confidence and change coping mechanisms to be adaptive.